Reactivity of molecular oxygen with aluminum clusters: Density functional and Ab Initio molecular dynamics simulation study. Issue 7 (20th January 2016) - Paranthaman, Selvarengan; Moon, Jiwon; Hong, Kiryong; Kim, Jeongho; Kim, Dong Eon; Kim, Joonghan; Kim, Tae Kyu
Abstract : Dissociative adsorption of molecular oxygen (O2 ) on aluminum (Al) clusters has attracted much interest in the field of surface science and catalysis, but theoretical predictions of the reactivity of this reaction in terms of barrier height is still challenging. In this regard, we systematically investigate the reactivity of O2 with Al clusters using density functional theory (DFT) and atom‐centered density matrix propagation (ADMP) simulations. We also calculate potential energy surfaces (PESs) of the reaction between O2 and Al clusters to estimate the barrier energy of this reaction. The M06‐2X functional gives the barrier energy in agreement with the one calculated by coupled cluster singles and doubles with perturbed triples (CCSD(T)) while the TPSSh functional significantly underestimates the barrier height. The ADMP simulation using the M06‐2X functional predicts the reactivity of O2 with the Al cluster in agreement with the experimental findings, that is, singlet O2 readily reacts with Al clusters but triplet O2 is less reactive. We found that the ability of a DFT functional to describe the charge transfer appropriately is critical for calculating the barrier energy and the reactivity of the reaction of O2 with Al clusters. The M06‐2X functional is relevant for investigating chemical reactions involving Al and O2 . © 2016 Wiley Periodicals, Inc. Abstract : The dissociative adsorption of molecular oxygen on aluminum surface is a fundamental process in surface science and in catalysis. Density functional theory calculations have been unable to achieve a consensus for the barrier heights in this reaction, with the uncertainty attributed to the effect of diffuse basis functions or spin states. The ability to predict the sizable barrier height is closely related to the ability describing the charge transfer character of the reaction.